KINERJA REPRODUKSI PADA SAPI MADURA DI BPTU-HPT PELAIHARI KALIMANTAN SELATAN - Dwi Dedeh Kurnia Sari; Yemima Yemima; Aprianda Renaldi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2026)
This study aimed to determine and evaluate the reproductive performance of Madura cattle reared at the Superior Livestock Breeding Center – Forage Feed Center (BPTU-HPT) Pelaihari, South Kalimantan. The research employed a survey method using a purposive sampling technique. Data were analyzed using descriptive statistical methods, including mean values and standard deviations. The observed parameters comprised Service per Conception (S/C), Conception Rate (CR), Calving Interval (CI), and Days Open (DO). The results indicated that the reproductive performance of Madura cattle at BPTU-HPT Pelaihari was categorized as good to moderately efficient. This suggests that the implementation of a standardized management system can enhance reproductive performance more effectively compared to conventional smallholder farming systems.